Analysis Of Fundamental Factors Of Financial Ratio To Increasing Stock Return In Manufacturing Companies In Indonesia Stock Exchange 2017-2020 - maulana majied sumatrani saragih, majied (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
This study aims to determine how the influence of the current ratio (CR), debt to equity ratio (DER), return on assets (ROA), total assets turnover (TATO), and price to book value (PBV) on stock returns. The results of hypothesis testing using multiple regression analysis and t-test indicate that: that the value is known that Current Ratio variable (X1) has a significant effect on the Stock Return variable (Y). the variable Debt to Equity Ratio (X2) has a significant effect on the Stock Return variable (Y). The Return On Asset (X3) variable has no significant effect on the Stock Return (Y) variable. variabel Total Asset turn Over (X4) berpengaruh signifikan terhadap variabel Return Saham (Y). variabel Price Book Value (X5) berpengaruh signifikan terhadap variabel Return Saham (Y). Variables Current Ratio (X1), Debt to Equity Ratio (X2), Return On Assets (X3), Total Assets Turn Over (X4), Price Book Value (X5) have a significant effect simultaneously (simultaneously) on the Stock Return variable ( Y).